The first synthesis of Crucigasterin 277—a polyunsaturated C-18 amino alcohol from the Mediterranean tunicate Pseudomonas crucigaster. Issue 30 (28th July 2016) - Flock, Solveig; Antonsen, Simen; Gallantree-Smith, Harrison; Langseter, Anne Marie; Skattebøl, Lars; Stenstrøm, Yngve
Abstract: Starting from eicosapentaenoic acid (EPA) andd -alanine, the first synthesis of (2 R, 3 S )-crucigasterin 277, a polyunsaturated C-18 amino alcohol from the Mediterranean tunicate, Pseudodistoma crucigaster, is described. Graphical abstract: